Relationship between Education Level and Mother's Knowledge about Choosing Contraceptive Devices - Rachma, Ulfie Aulia; Ariningtyas, Ninuk Dwi; Levani, Yelvi; Anas, Muhammad; Urrachman, Salsabillah Kemangi (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background: Population growth is influenced by high birth rates and low mortality rates. Improved health services reduce mortality rates while births continue to increase. According to the Data and Information Center of the Indonesian Ministry of Health (2020), contraceptive services include education, counseling, medical screening, provision and removal of contraceptives, and handling of side effects to prevent pregnancy.Objective: To determine the relationship between the level of education and mothers' knowledge of contraception at Bandar Kedungmulyo Community Health Center, Jombang.Method: This is an analytical observational study aimed at analyzing the relationship between the level of education and the level of a mother's knowledge of the choice of contraception. The study sample consisted of 304 women of childbearing age who accepted family planning. Data were collected using a questionnaire.Results: The majority had good knowledge (97.7%). Injectable contraception was the most widely chosen (60.5%). The Chi-square test and multinomial logistic regression showed that the level of education and knowledge of mothers influenced the choice of contraception.Conclusion: There is a relationship or simultaneous influence between the level of education and the level of knowledge of mothers on the choice of contraceptives.